Semiotic Analysis and Gender Representation in Nike's Advertisement “What If You Can" - Veronica Nurma; Gina Valerina; Leonardus Wahono Kurniawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study examines Nike's advertisement "What If You Can?" through a semiotic and sociocultural approach, focusing primarily on gender representation and women's empowerment in the context of sport, particularly in the Middle East. This advertisement is interesting because it presents a narrative of Muslim women actively participating in sports, a discourse that often faces cultural and social challenges in the region. Using Roland Barthes's semiotic theory, this study analyzes the visual and textual signs contained in the advertisement to interpret their denotative and connotative meanings. This approach reveals how these signs shape the social construction of gender roles, as well as convey implicit and explicit motivational and empowering messages. Within the framework of a constructivist paradigm, this study emphasizes the importance of subjective interpretation of the existing signs, in order to uncover the deeper meanings hidden behind the visual representation. Furthermore, a critical approach is also used to assess the extent to which this Nike advertisement challenges established gender stereotypes, or even subconsciously reinforces them. This research focuses not only on the content of the advertisement, but also on the social and cultural context in which the advertisement is disseminated, particularly public perceptions of women's involvement in sports in the Middle East. A qualitative analysis was conducted on key elements in the advertisement, such as symbols, colors, narratives, and gestures, to identify how gendered meanings are constructed and conveyed. This research is expected to contribute to academic discourse on gender representation in the media, as well as its social implications for public attitudes toward women's equality and empowerment. Thus, this study demonstrates how Nike's visual communication strategy can play a role in shaping public perceptions regarding the role of women in modern sport.